Agile transformation: what is it about? - Gandomani, Taghi Javdani; Zulzalil, Hazura; Nafchi, Mina Ziaei (IEEE, 2014)
Agile software development by offering new values motivates software companies to use Agile methods instead of traditional methods. However, reviewing the literature shows that leaving traditional methods and moving to Agile methods is subjected to many serious challenges. We have conducted a large-scale research study to empirically discover various aspects of Agile transformation. Our Grounded Theory study showed the general outline of Agile transformation. The main aim of this paper is to figure out the most important concepts that need to be considered when moving to Agile. This study showed that Agile transformation comprises many concepts, activities, and steps including transformation prerequisites, facilitators, framework, assessment, coaching, and so on. Companies need to be familiar with these concepts before starting transitioning to Agile.